Reimagining Reproductive Rights Jurisprudence in India: Reflections on the Recent Decisions on Privacy and Gender Equality from the Supreme Court of India - Jain, Dipika; Shah, Payal K. (Columbia Journal of Gender and Law, 2020)
Abstract